EFEKTIFITAS MOM LOVA POCKET BOOK SEBAGAI MEDIA PROMOSI KESEHATAN MENTAL PADA IBU HAMIL - Lailiyana; Septi Indah Permata Sari; Findy Hindratni; Diyan Maria Kristin (JOMIS (Journal of Midwifery Science), 2026)
The World Health Organization reports that approximately 10% of pregnant women and 15% of women who have just given birth experience mental health problems, especially depression. The purpose of this study was to determine the effectiveness of the Mom Lova pocket book as a medium for promoting mental health in pregnant women. The type of research conducted was quantitative research with a quasi-experimental design. The study population was all pregnant women in the pregnancy class. The sample was taken using the Cluster sampling technique, with a total sample size of 54 pregnant women from all pregnancy classes in the selected cluster (Community Health Center). The results of the study showed that the average increase in knowledge of pregnant women about mental health in the group of pregnant women given education using the Mom Lova pocket book was higher, namely 26.92 with a SD of 13.20, compared to the group educated using leaflets, namely an average increase of 18.08 with a SD of 11.67. The results of the Mann-Whitney statistical test showed that there was a difference in the average increase in knowledge of mental health among pregnant women between the groups given education using the Mom Lova pocketbook and those given leaflets (p = 0.017). The use of media is very important in providing education to the community. The more engaging the media is, the more it will be accepted by users and will increase motivation to learn and understand its contents. The Mom Lova pocket book is an innovative pocket book based on Augmented Reality (AR) technology that helps visualize abstract concepts for understanding and the structure of an object model in greater detail and realism, making it more engaging, piquing the target audience's interest, and enhancing comprehension of the message. Mom Lova will help mothers become more aware of their mental health and provide them with the support they need